ANALISIS ORIENTASI PASAR DAN STRATEGI BAURAN PEMASARAN PENGUSAHA ROTI DI KOTA BENGKULU - Gabrienda, Gracia; Nusril, Nusril; Badrudin, Redy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research is aimed at investigating market posisition and market orientation of bakery producers, and designing mix marketing strategy for bakery producers in Bengkulu city. Four bakery producers, namely Surya Bakery, Bake Mart, Karina Bakery and Ais Bakery, are selected purposively as subject of this study. Sixty eight respondents are selected using accidental sampling method for UAI survey, and 4 respondents for each bakery. Relative Market Share and descriptive analysis are used to analyse data obtained from survay. The research found that Surya Bakery can be categorised as market leader, while Bake Mart, Karina Bakery, and Ais Bakery as market challanger, market follower, and market nicher respectively. All bakery producers has custumer orientation. The study also concluded that Surya Bakery should enlarge its market and intisifies promotion, Bake Mart should enlarge its distribution network, Karina Bakery should expose its specific shop and Ais Bakery should find new market segment.